Detection of foreign objects in milk using an ultrasonic system - Mohd Taufiq Mohd Khairi; Sallehuddin Ibrahim; Mohd Amri Md Yunus; Ahmad Ridhwan Wahap (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents the utilization of an ultrasonic sensing system to detect foreign objects in milk. The advantage of an ultrasonic system is that it is low cost and it can detect a wide range of materials. A foreign body is any contaminated object found in food. Because of the scale of multifarious food processing levels and distribution, the utilization of the food product are sometimes difficult to control, which will inevitably lead to some complaints by consumers. Milk is widely consumed in the world as it is considered as a healthy drink due to it is high nutrients levels. However, from time to time cases of milk contamination are reported. In this paper. the relationship between the foreign bodies in terms of their dimensions and the resultant amplitude are presented. Mathematical modelling were carried out based on two ultrasonic parameters i.e. acoustic impedance and wave amplitude utilizing several types of foreign bodies with different dimensions. Three types of foreign bodies which are steel, rubber and air were investigated to determine the voltage amplitude detected by the ultrasonic receiver when the foreign bodies obstructed the ultrasonic wave propagation path. The diameters of foreign bodies were in the range from 4 mm to 11 mm. The results showed good correlations between the receiver voltage and the size of foreign bodies with correlation coefficients greater than 0.95. Each foreign body also demonstrated different voltage amplitudes when several sizes of the foreign bodies were tested which showed the ability of the system to distinguish the size of each foreign body.